2019
DOI: 10.1002/mnfr.201801060
|View full text |Cite
|
Sign up to set email alerts
|

Robust Markers of Coffee Consumption Identified Among the Volatile Organic Compounds in Human Urine

Abstract: Scope:The human volatilome has gained high interest for the discovery of potential biomarkers of diseases. However, knowledge about the diet as a crucial factor affecting the volatilome is scarce. Therefore, the search for disease biomarkers, as well as the potential use of volatiles as dietary markers is so far limited. The aim of this study is to investigate the association of the diet with the urinary volatilome with the special task to find potential markers of coffee consumption in 24 h urine samples from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 58 publications
0
16
0
Order By: Relevance
“…In the context of biofluids, SPME in HS mode is the second most popular technique for volatile analytes characterization by GC×GC [43–46]. Mack et al.…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of biofluids, SPME in HS mode is the second most popular technique for volatile analytes characterization by GC×GC [43–46]. Mack et al.…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
“…Mack et al. evaluated the efficiency of different HS‐SPME fibers to measure urinary volatile metabolites linked to dietary intake [43]. As can be seen in Figure 4, a richer chromatogram and higher extraction yields were obtained when using the triphasic DVB/CAR/PDMS fiber, with the authors pointing out the importance of careful evaluation and optimization of the materials/conditions for analyte extraction.…”
Section: Non‐targeted Analysis Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are a few studies also performed the nontargeted screening approaches for screening and semiquantification (or relative quantification) of a huge number of VOCs in human specimens, specifically in urine and breath samples [45,56,57]. To distinctly identify a real smoking habit and/or event, Capone et al.…”
Section: Resultsmentioning
confidence: 99%
“…Further, to delineate the role of diet (especially coffee consumption) as a crucial factor affecting the VOCs composition, Mack et al. conducted a detailed biomonitoring research via Karlsruhe Metabolomics and Nutrition (KarMeN) study [57]. Overall, they detected 138 VOCs and they found that six of them could serve as potential biomarkers of coffee consumption, particularly 3,4‐dimethyl‐2,5‐furandione as the most promising biomarker.…”
Section: Resultsmentioning
confidence: 99%